Signing for the deaf using virtual humans - Bangham, J A; Cox, Stephen; Lincoln, Michael; Marshall, I; Tutt, M; Wells, Mark (IEEE Signal Processing Society Press, 2000)
Research at Televirtual (Norwich) and the University of East Anglia, funded predominantly by the Independent Television Commission and more recently by the UK Post Office also, has investigated the feasibility of using virtual signing as a communication medium for presenting information to the deaf. We describe and demonstrate the underlying virtual signer technology, and discuss the language processing techniques and discourse models which have been investigated for information communication in a transaction application in Post Offices, and for presentation of more general textual material in texts such as subtitles accompanying television programmes